Analisis Kebutuhan Pengembangan Soal HOTS dalam Pembelajaran Teks Pidato Persuasif di MGMP SMP Wilayah Kabupaten Bantul - Himawan, Riswanda; Suyata, Pujiati (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
Learning Indonesian in the era of the industrial revolution 4.0 requires students to be able to master various skills, one of which is critical thinking skills. Teachers as learning facilitators must be able to guide students in mastering these skills. One of the efforts that teachers can make in achieving this is to familiarize students with higher-order thinking, through various kinds of HOTS-based evaluation questions. At the initial stage, it is necessary to know the needs analysis related to the development of HOTS questions in Indonesian language learning materials for persuasive speech texts. Needs analysis in this study is part of research and development (R&D). The method used in this research is the survey method. Data was collected by observation, interviews and document analysis. The data obtained in this study are qualitative data. The qualitative data was then analyzed descriptively. The results of the needs analysis show that the teachers in the MGMP area of ​​the Indonesian Junior High School in Bantul Regency really need HOTS questions in procedural text learning as a teacher reference in making and presenting HOTS questions to students. The results of the study show that so far the teacher has never implemented it, and the students have never worked on HOTS-based evaluation questions in Indonesian language learning materials for persuasive speech texts.